(untitled) (Circe de clásicos y modernos, 2025)
This work aims to advance the study of the color saffron (κροκός) in ancient Greek literature, considering literary sources in conjunction with archaeological evidence, which implies the methodological separation between color and dye. The main aim is to demonstrate that an interdisciplinary approach taking into account the material dimension of color is essential to analyze the symbolic dimension of passages such as that of the sacrifice of Iphigenia in Aeschylus’ Agamemnon (vv. 238-247). Finally, the relationship between this passage and the HH II is proposed, based on the mentions of κροκός in both texts, which link the characters of Iphigenia and Persephone.